FAQs - Special Olympics Australia Vaccination Policy - Special Olympics Australia (2022)
We unequivocally support the public health orders in place to protect vulnerable communities against COVID-19. People with intellectual disabilities are a high-risk group for COVID-19 illness, complications, and death and we urge everyone to get vaccinated. From 1 February 2022, double COVID-19 vaccination will be a minimum condition of participation, attendance, entry, volunteering, and employment with Special Olympics Australia. In addition, our activities and events will all continue be conducted with a strict adherence to relevant public health orders. We will continue to monitor information and advice and adjust our COVID Safety Plans as required, to keep the Special Olympics community safe.